2022
DOI: 10.3390/biology11030412
|View full text |Cite
|
Sign up to set email alerts
|

How Do Hexokinases Inhibit Receptor-Mediated Apoptosis?

Abstract: The regulated cell death apoptosis enables redundant or compromised cells in ontogeny and homeostasis to remove themselves receptor-dependent after extrinsic signaling or after internal stress by BCL-2 proteins on the outer mitochondrial membrane (OMM). Mitochondrial BCL-2 proteins are also often needed for receptor-mediated signaling in apoptosis. Then, the truncated BH3-only protein BID (tBID) blocks retrotranslocation of the pro-apoptotic BCL-2 proteins BAX and BAK from the mitochondria into the cytosol. BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 119 publications
0
5
0
Order By: Relevance
“…2 B). On the other hand, upregulation of neocortical HK1 induced by DEX and DES might suggest antiapoptotic regulatory HK1 interaction with VDACs [ [53] , [54] , [55] ]. In addition, the significant upregulation of neocortical GSTA4 might imply regulation of increased oxidative stress [ 56 ] in a response to DEX and DES anesthesia ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 B). On the other hand, upregulation of neocortical HK1 induced by DEX and DES might suggest antiapoptotic regulatory HK1 interaction with VDACs [ [53] , [54] , [55] ]. In addition, the significant upregulation of neocortical GSTA4 might imply regulation of increased oxidative stress [ 56 ] in a response to DEX and DES anesthesia ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial membrane-bound HK2 exerts anti-neoplastic cytoprotective effect by decreasing mitochondrial BAX accumulation. 40 In fact, HK2 has been found to resist indomethacin-induced cytochrome c release and caspase-3 activation. 41 Further, SIRT3 overexpression might also affect the redox homeostasis in cancer cells by over-suppression of reactive prooxidants level (owing to its multidimensional antioxidant effects), which could be also detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…7B ). In previous studies, HK1 was shown to inhibit apoptosis by interacting with voltage-dependent anion channel-1 and other pro-apoptosis BCL family proteins on mitochondria [ 55 , 56 ]. Furthermore, previous study has shown that by reducing hexokinase 2, resveratrol and dioscin are able to inhibit glycolysis and induce apoptosis in HCC cells and colorectal cancer cells, respectively [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%